Penerapan Model Pembelajaran Flipped Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi di SMAN 7 Padang - Vivi Dianofutri; Tri Kurniawati (Jurnal Salingka Nagari, 2023)
This study aims to improve student achievement with the flipped learning model. This research was conducted on economic subjects at SMA Negeri 7 Padang. This research is a Classroom Action Research (CAR) and the research subjects are students of class XI IPS 2 totaling 35 students consisting of 17 male students and 18 female students. The research was carried out in two cycles, namely, cycle I and cycle II. The data collection technique used the results of the cognitive domain test in the form of an objective test. Based on the results of the study, the average student achievement of XI IPS 2 in the first cycle was 69 with the percentage of classical completeness of students was 48.57. While the average student achievement obtained in the second cycle is 79 with the percentage of classical completeness of students being 77.14%. So it can be concluded that student achievement by applying the flipped learning model to economics subjects in class XI IPS 2 at SMAN 7 Padang has increased.